2020
DOI: 10.1088/1755-1315/485/1/012093
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Portfolio Assessment in English Writing Classes

Abstract: The research goals were to (1) identify the teacher’s perspective about the characteristics and practices of portfolio assessment in English writing classes, and (2) investigate the enactment of portfolio assessment in English writing classes. The research design was a case study, and it was conducted at a junior high school in Jember. Moreover, the data were obtained from observation, interview, and document analysis. In analyzing data, Miles and Huberman’s model was considered to be used through data reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…This finding is supported by Ankwai (2022), who mentioned that the Saudi curricula do not focus much on English writing skills. All these weaknesses of portfolio assessment stated earlier are in line with other studies (Hudori et al, 2020;Kao, 2015). Hence, the qualitative data analysis offers several suggestions for how ESL teachers can assess PA successfully to help Saudi students overcome the barriers they face using the writing portfolio.…”
Section: Discussionsupporting
confidence: 76%
“…This finding is supported by Ankwai (2022), who mentioned that the Saudi curricula do not focus much on English writing skills. All these weaknesses of portfolio assessment stated earlier are in line with other studies (Hudori et al, 2020;Kao, 2015). Hence, the qualitative data analysis offers several suggestions for how ESL teachers can assess PA successfully to help Saudi students overcome the barriers they face using the writing portfolio.…”
Section: Discussionsupporting
confidence: 76%
“…In relation to that, Lam and Lee (2010) reported portfolio assessment is less threatening and much more supportive of student learning than timed, impromptu essay tests. In addition, the finding also mirror Hudori et al, (2020) results of study where they found that assessing writing by using portfolio assessment is good and useful as it provides positive effects to the quality of teaching and learning process in English classes. Therefore, portfolio assessment brings some benefits which can be addressed to both students and English educators.…”
Section: Signs Of Autonomous Learning Initiativessupporting
confidence: 73%
“…The practitioners belonging to such fields use portfolios for organizing and record keeping of their best work to further showcase their work and achievements in both academic fields and their world of jobs. Portfolios assess and appraise the progress of achievement in life as well as at job place (Hudori, Tasnim, & Fardhani, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Students' portfolio development is infused in assessment practices as a purposeful activity that may be used to assess the progress of the student. Therefore, it is desirable for an effective portfolio to include maximum participation by the student in a collection of his work, content selection, content selection criteria, and criteria to judge his own work and ultimately enable him for enduring participation in self-reflection (Hudori et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%